A Força da empatia em Edith Stein: uma maneira de viver e sentir. - Santos, Patrícia Cristiane de Santana (2023)
The dissertation presents the theme of "The Power of Empathy in Edith Stein: A Way of Feeling and Living Life". The investigation of this theme calls for an analysis of the phenomenon of empathy and its importance for living in a community guided by ethics, and the resulting care, responsibility, recognition of others as hu- man beings with their own unique qualities, and the ability to recognize oneself in others. Edith Stein is a philosopher who sheds light on ethical thinking through her work on empathy, emphasizing that the universe of one's own "self" cannot override the universe of another's "self". It is a meeting of experiences that requires reflection on one's position in the world. First off, as Edith Stein is introduced, her life's trajec- tory is presented, and despite the growing interest in her thoughts, special recognition is given to this woman who lived in pursuit of truth and brought her own life expe - rience into her philosophy. Secondly, as theoretical foundation, the dissertation uses phenomenology for understanding empathic acts that enable encounters between experiences. Following this, the ethical issue of care is discussed, establishing a dia- logue between Leonardo Boff and Edith Stein, and subsequently presenting the ethics of alterity as a meeting between the thoughts of Levinas and the phenomenol- ogist. Finally, the ethics of responsibility in Edith Stein is discussed, drawing on her work on empathy and calling for care and encounters between people who, in their uniqueness and freedom, must act ethically.